Long-term follow-up of children treated for cancer: why is it necessary, by whom, where and how?. Issue 3 (2nd March 2007) - Skinner, Roderick; Wallace, W Hamish B; Levitt, Gillian
Abstract : About 1 in 715 young adults is a survivor of childhood malignancy, but these individuals are at increased risk of considerable treatment-related morbidity or even mortality. A recent study suggests that at least 60% have one or more chronic health problems, whilst about 20% have three or more. The principle goal of long-term follow-up (LTFU) of survivors is to decrease the severity of late treatment complications by performing appropriate surveillance to detect incipient toxicity, and by facilitating timely diagnosis and management of emerging or established late adverse effects. The content of LTFU is dictated by the type and amount of treatment for the malignancy, and has been defined in recent clinical guidelines. Moreover, LTFU allows provision of survivor education, psychosocial support and health promotion advice. However, considerable variation exists in how LTFU is performed, with several alternative models involving a range of professionals in a variety of locations, depending on numerous clinical and organisational factors. There is increasing utilisation of multidisciplinary teams, and recognition of the importance of effective transition strategies whereby care is transferred to more age-appropriate providers, usually after a period of joint care in adolescence. It is of paramount importance to ascertain and meet the needs of survivors themselves.